2018
DOI: 10.1007/s00464-018-6094-3
|View full text |Cite
|
Sign up to set email alerts
|

Visual spatial ability for surgical trainees: implications for learning endoscopic, laparoscopic surgery and other image-guided procedures

Abstract: Two percent of surgical trainees performed statistically significantly worse than their peers on visual spatial ability. The implication of this finding is unclear, further research is required that can look at the learning and educational portfolios of these trainees who perform poorly on visual spatial ability, and ascertain if they are struggling to learn skills for image-guided procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…However, if VSA is only correlated with surgical performance in novices, it suggests that VSA may be a fluid, and trainable characteristic, and has the potential to be acquired throughout residency training with practice 3 We believe that if VSA is a trainable characteristic, high VSA should not be a requirement for those applying to surgical residencies. 12,15,53,108 To address this concern, future research should focus on correlating VSA to surgical performance across all levels of training. One way to achieve this would be to measure trainees' performance on a VSA test (e.g., MRT, CC Test, or CR Test) and performance on surgical simulations annually to identify a pattern across years of training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if VSA is only correlated with surgical performance in novices, it suggests that VSA may be a fluid, and trainable characteristic, and has the potential to be acquired throughout residency training with practice 3 We believe that if VSA is a trainable characteristic, high VSA should not be a requirement for those applying to surgical residencies. 12,15,53,108 To address this concern, future research should focus on correlating VSA to surgical performance across all levels of training. One way to achieve this would be to measure trainees' performance on a VSA test (e.g., MRT, CC Test, or CR Test) and performance on surgical simulations annually to identify a pattern across years of training.…”
Section: Discussionmentioning
confidence: 99%
“…Six other articles supported this notion due to the correlation between psychomotor ability and performance of surgical trainees found in the literature. 4,15,38,[87][88][89] Two articles describe a suite of tests that can be used to screen candidates. 90,91 However, thirteen studies suggested further research is required before VSA testing is incorporated into e116 surgical residency applications as there remains some conflicting evidence surrounding VSA and surgical performance.…”
Section: Theme One: Vsa and Surgical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The ability to perceive the relationships between structures as well as the use of surgical instruments is of crucial importance among healthcare workers and especially among medical care professionals (i.e., surgeons, nurses). Healthcare workers are constantly relying on their visuospatial abilities in order to care for their patients as they are required to use techniques that involve manipulation of medical instruments ( 16 ), they need to have excellent hand-eye coordination ( 17 ) and great perception of spatial anatomy ( 18 ). Furthermore, considering the constant technological advances that necessitate the ability of healthcare workers to learn new technical skills, visuospatial abilities can be of importance for acquiring these skills ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinicians need to receive three-dimensional (3D) spatial thinking training before performing endoscopic surgery. 1,2 Lumbar disc herniation (LDH) treatment is an important ABBREVIATIONS 2D = two-dimensional; 3D = three-dimensional; LDH = lumbar disc herniation; PETD = percutaneous endoscopic transforaminal discectomy; VR = virtual reality.…”
mentioning
confidence: 99%